How do episodic and semantic memory contribute to episodic foresight in young children? - Martin-Ordas, Gema; Atance, Cristina M.; Caza, Julian S. (Frontiers in Psychology, 2014)
Humans are able to transcend the present and mentally travel to another time, place, or perspective. Mentally projecting ourselves backwards (i.e., episodic memory) or forwards (i.e., episodic foresight) in time are crucial characteristics of the human memory system. Indeed, over the past few years, episodic memory has been argued to be involved both in our capacity to retrieve our personal past experiences and in our ability to imagine and foresee future scenarios. However, recent theory and findings suggest that semantic memory also plays a significant role in imagining future scenarios. We draw on Tulving’s definition of episodic and semantic memory to provide a critical analysis of their role in episodic foresight tasks described in the developmental literature. We conclude by suggesting future directions of research that could further our understanding of how both episodic memory and semantic memory are intimately connected to episodic foresight.